ANTESEDEN DAN KONSEKUENSI LOYALITAS KARYAWAN - Rini Juni Astuti; Haura Dian Syafiqah Siregar (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study is to investigate the factors that influence employee loyalty at Bank XX North Sumatra Trade Branch Office as antecedents. These factors include transformational leadership and organizational trust. And the impact or consequence on employee performance. The method used in this research is quantitative descriptive method. This research is expected to contribute in both theoretical and practical fields. Data processing and hypothesis testing of this study using SEM-PLS software and SmartPLS 4. This shows that the results of transformational leadership have a positive and significant effect on employee loyalty. Organizational trust has a positive and significant effect on employee loyalty. Employee loyalty has a positive and significant effect on employee performance. Employee loyalty has a positive and significant effect on employee performance. The results of the study providea more effective humanresource management strategy to improve employee loyalty and performance. Suggestions that can be given in this study are to increase concern for employees' lives, provide opportunities to give opinions, uphold the company's vision and mission, and improve their performance in completing tasks